Zur Rauhhautfledermaus (Pipistrellus nathusii Keyserling & Blasius, 1839) in den nordbadischen Rheinauen. - Arnold, Andreas; Scholz, Annette; Storch, Volker; Braun, Monika (Zenodo, 1996)
(Uploaded by Plazi for the Bat Literature Project) The Nathusius'bat in flood plain forests in Nordbaden (SW-Germany) A control of bird and bat boxes during the autumns of 1994 and 1995 resulted in proving the occurrence of numerous Nathusius' bats (Pipistrellus nathusii KEYSERLING & BLASIUS, 1839) in the northwestern part of the county of Baden-Wuerttemberg. The boxes controlled were located in flood plain forests along the river Rhine. The majority of specimens was found in forest areas close to the river. In forests more distant from the river Rhine the number of bats decreased.